Sample for the Inner Control on the Quality In Accordance With Standard - Thijeel, Ali Mohammed; Rashid Bachay, Imtithal (Opción, 2019)
The aim of the research is to design a proposed model for internal quality audit in accordance with ISO 19011:2011 via comparative qualitative research methods. As a result, the objectives of the company was not documented at the level of each department or division in the company, but the general goals of the company as a whole were documented. In conclusion, ISO 19011:2011 for quality enables the auditor to know the strengths and weaknesses of the quality management system and thus identify the preventive and corrective measures and areas of improvement.